Influence of β-adrenoceptor antagonists on the pharmacokinetics of rizatriptan, a 5-HT(1B/1D) agonist: differential effects of propranolol, nadolol and metoprolol - Goldberg, Michael R (Blackwell Science Inc, 2001)
AIMS: Patients with migraine may receive the 5-HT(1B/1D) agonist, rizatriptan (5 or 10 mg), to control acute attacks. Patients with frequent attacks may also receive propranolol or other β-adrenoceptor antagonists for migraine prophylaxis. The present studies investigated the potential for pharmacokinetic or pharmacodynamic interaction between β-adrenoceptor blockers and rizatriptan. METHODS: Four double-blind, placebo-controlled, randomized crossover investigations were performed in a total of 51 healthy subjects. A single 10 mg dose of rizatriptan was administered after 7 days' administration of propranolol (60 and 120 mg twice daily), nadolol (80 mg twice daily), metoprolol (100 mg twice daily) or placebo. Rizatriptan pharmacokinetics were assessed. In vitro incubations of rizatriptan and sumatriptan with various β-adrenoceptor blockers were performed in human S9 fraction. Production of the indole-acetic acid-MAO-A metabolite of each triptan was measured. RESULTS: Administration of rizatriptan during propranolol treatment (120 mg twice daily for 7.5 days) increased the AUC(0,∞) for rizatriptan by approximately 67% and the C(max) by approximately 75%. A reduction in the dose of propranolol (60 mg twice daily) and/or the incorporation of a delay (1 or 2 h) between propranolol and rizatriptan administration did not produce a statistically significant change in the effect of propranolol on rizatriptan pharmacokinetics. Administration of rizatriptan together with nadolol (80 mg twice daily) or metoprolol (100 mg twice daily) for 7 days did not significantly alter the pharmacokinetics of rizatriptan. No untoward adverse experiences attributable to the pharmacokinetic interaction between propranolol and rizatriptan were observed, and no subjects developed serious clinical, laboratory, or other significant adverse experiences during coadministration of rizatriptan with any of the β-adrenoceptor blockers. In vitro incubations showed that propranolol, but not other β-adrenoceptor blockers significantly inhibited the production of the indole-acetic acid metabolite of rizatriptan and sumatriptan. CONCLUSIONS: These results suggest that propranolol increases plasma concentrations of rizatriptan by inhibiting monoamine oxidase-A. When prescribing rizatriptan to migraine patients receiving propranolol for prophylaxis, the 5 mg dose of rizatriptan is recommended. Administration with other β-adrenoceptor blockers does not require consideration of a dose adjustment.